Forum młodych chirurgówStandard and logistic EuroSCORE risk evaluation in isolated aortic and mitral valve surgery: Is it time for review? - Olszówka, Piotr; Szafranek, Adam; Young, Neil; O’Keefe, Peter A. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim: To assess the accuracy of EuroSCORE in stratifying perioperative risk in isolated aortic and mitral valve surgery. Material and methods: Between January 2000 and December 2006, 515 patients underwent aortic valve surgery (AVR group) and 228 patients underwent mitral valve surgery (MVR group). Data were prospectively collected. The association of perioperative risk factors with outcome was investigated in both groups. A comparison of EuroSCORE predicted vs. observed mortality was made. Results: Patients in the AVR group were older than those in the MVR group; 65.3 years (SD 12.0) vs. 60.7 (SD 12.2) (p < 0.001); more frequently had extracardiac arteriopathy; 5.4% vs. 2.2% (p = 0.024), and poor preoperative ejection fraction; 9.5% vs. 4.4% (p = 0.009). There was no difference in additive EuroSCORE 5.9 (SD 2.9) vs. 6.2 (SD 3.3) and logistic EuroSCORE 9.1 (SD 10.1) vs. 9.1 (SD 13.3). Parsonnet score was higher in the AVR group, 13.2 (SD 7.2) vs. 11.2 (SD 5.8) (p < 0.001). The MVR group were more frequently females, 53.1% vs. 40.9% (p = 0.001); patients who underwent a redo operation, 16.7% vs. 8.5% (p = 0.001); had infective endocarditis, 9.6% vs. 5.2% (p = 0.013); and critical preoperative state, 7.9% vs. 1.9% (p < 0.001). 30-day mortality in the AVR group was 2.9% and 5.3% in the MVR group (p = 0.057). Conclusions: In both groups, observed mortality was less than that predicted by both additive and logistic EuroSCORE, however it was more accurate in the MVR group.